The nexus between teacher trainees’ digital literacy and online learning motivation - Md. Meraz Ahmed; Merine Sultana; Md. Rokonuzzaman; Md. Kamal Hossain (AAOU Journal)
Purpose – This study examined the relationship between levels of digital literacy and the online learning motivation (OLM) of teacher trainees across various factors. Design/methodology/approach – This investigation utilized a quantitative research approach. The sample was selected through a purposive method and consisted of 485 teacher trainees from the School of Education at Bangladesh Open University (BOU). Participants' digital literacy and OLM were assessed using validated five-point Likert scale questionnaires, consisting of 17 items for digital literacy and six items for OLM. The collection of data was conducted via a cross-sectional survey. Descriptive analysis, Cronbach’s alpha, exploratory factor analysis, t-test and ANOVA were employed for the purpose of data analysis. Findings – The findings demonstrated that teacher trainees possessed sufficient digital literacy and OLM concerning the specified variables. Furthermore, there was a significant correlation between digital literacy and OLM. BOU can evaluate all of these findings to make a rational decision regarding the development of its teacher education programs. Originality/value – This exploratory study has yielded significant insights into the demographic characteristics, computer and internet skills, virtual learning skills and OLM of teacher trainees, thereby enhancing the existing body of knowledge in this field.